Biologia da Arsenura xanthopus (Walker, 1855) ( Lepidoptera - Adelocephalidae ), praga do «Açoita-Cavalo» (Luehea spp.) e notas sôbre seus inimigos naturais - Lordello, Luiz Gonzaga E.; Mariconi, Francisco A. Menezes (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
Biology of Arsenura xanthopus (Walker, 1855) (Lep., Adelocephalidae), a pest of Luehea spp. (Tiliaceae), and notes on its natural enemies. In the beginning of 1950, one of the Authors made some observations about the biology of Arsenura xanthopus (Walker), in Piracicaba, State of S. Paulo, Brazil. From 1951 to 1953, both Authors continued the observations on such an important Adelocephalidae, the caterpillars of which represent a serious pest of Luehea spp. leaves. Actually, in some occasions, the caterpillars can destroy completely the leaves of the trees. The species is efficientely controlled by two natural enemies: an egg parasite (Tetrastichus sp., Hym., Eulophidae) and a fly attacking the last instar caterpillar (Winthemia tricolor (van der Wulp), Dip., Tachinidae). Tetrastichus sp. can destroy 100% of the eggs and the fly, 70 to 100% of the caterpillars. Indeed, facts as such are very interesting because we rarely know of a case of so complete a control of a pest by an insect. A. xanthopus had not yet been mentioned in our literature. Actually neither the systematic bibliography nor the economic one has treated of this species. However, a few other species of Arsenura are already known as living on Luehea spp. According to the Authors' observations, W. tricolor was also unknown by the Brazilian entomological literature. Arsenura xanthopus (Walker, 1855) After giving the sinonimy and a few historical data concerning the species, and its geographical distribution, the Authors discuss its placing in the genus Arsenura Duncan or Rhescyntis Huebner, finishing by considering Arsenura xanthopus as a valid name. The Authors put the species in the family Adelocephalidae, as it has been made by several entomologists. The host plant The species of Tiliaceae plants belonging to the genus Luehea are called "açoita-cavalo" and are well known for the usefulness of their largely utilized wood. The genus comprises exclusively American plants, including about 25 species distributed throughout the Latin America. Luehea divaricata Mart, is the best known species and the most commonly cultivated. Biology of Arsenura xanthopus Our observations show that the species passes by 6 larval stages. Eggs and egg-postures, all the 6 instars of the caterpillars as well as the chrysalid are described. The pupal period is the longest of the cycle, taking from 146 to 256 days. Data on the eclosion and habits of the caterpillars are also presented. A redescription of the adult is also given. Our specimens agreed with BOUVIER's description, except in the dimension between the extremities of the extended wings, which is a little shorter (107 mm according to BOUVlErVs paper against from 80 to 100mm in our individuals). Winthemia tricolor (van der Wulp, 1890) Historical data, geographical distribution and host are first related. W. tricolor had as yet a single known host-; Ar^-senura armida (Cramer). This chapter also contains some observations on the biolcn gy of the fly and on its behaviour when trying to lay eggs on the caterpillars' skin. The female of W. tricolor lays from 1 to 33 eggs on the skin of the last instar caterpillar. The mam region of the body where the eggs are laid are the membranous legs. Eggs are also very numerous oh the ventral surface of the thorax and abdomen. The. preference for such regions is easily cleared up considering the position assumed by the caterpillar when fixed motionless in a branch. In such an occasion, the fly approaches, the victim, puts the ovipositor out and lays the eggs on different parts of the body, mainly on the mentioned regions, which are much more easily reached. The eggs of the fly are firmly attached to the host's skin, being almost impossible to detach them, without having them broken. The minute larvae of the fly enter the body of, the host when it transforms into chrysalid. Chrysalids recentely formed and collected in nature f requentely show a few small larvae walking on its skin and looking for an adequate place to get into the body. A few larvae die by remaining in the skin of the caterpillar which is pushed away to some distance by the active movements of the chrysalid recentely formed. From 1 to 10 larvae completely grown may emerge from the attacked chrysalid about 8 days after their penetrating into the caterpillars' body and soon begin to look for an adequate substratum where they can transform themselves into pupae. In natural conditions, the metamorphosis occurs in the soil. The flies appear within 15 days. Tetrastichus sp. This microhymenoptera is economically the most interesting parasite, being commonly able to destroy the whole pos^ ture of the moth. Indeed, some days after the beginning of the infestation of the trees, it is almost impossible to obtain postures completely free of parasites. The active wasp introduces the ovipositor into the egg of the moth, laying its egg inside, from 80 to 120 seconds after having introduced it. A single adult wasp emerges from each egg. Sarcophaga lambens Wiedemann, 1830 During the observations carried out, the Authors obtained 10 flies from a chysalid that were recognized as belonging to the species above. S. lambens is a widely distributed Sarcophagidae, having a long list of hosts. It is commonly obtained from weak or died invertebrates, having no importance as one of their natural enemies. Sinonimy, list of hosts and distribution are presented in this paper. Control of Arsenura xanthopus A test has been carefully made in the laboratory just to find out the best insecticide for controlling A. xanthopus caterpillars. Four different products were experimented (DDT, Pa-rathion, BHC and Fenatox), the best results having been obtained with DDT at 0,25%. However, the Authors believe in spite of the initial damages of the trees, that the application of an insecticide may be harmful by destroying the natural agents of control. A biological desiquilibrium may in this way take place. The introduction of the parasites studied (Tetrastichus sp. and Winthemia tricolor) seems to be the most desirable measure to fight A. xanthopus.